Pengaruh Kemampuan Membaca dan Motivasi Belajar Terhadap Kemampuan Pemecahan Masalah pada Soal Cerita Matematika - Kristiani, Dini; Tupulu, Nasri (Papanda, 2025)
This research aims to find out whether there is an influence of students' reading ability and learning motivation on the ability to solve mathematical story problems. This study uses quantitative research with a descriptive approach. This research uses data collection techniques, namely test methods, questionnaire methods, and documentation. This research was carried out at GKE Sidas Junior High School with a population of 58 people in grade 7 and a sample of 30 respondents. The results of the study showed that there was an influence of reading ability and learning motivation on problem-solving skills in mathematics story problems of GKE Sidas Junior High School students. The hypothesis test is proven by the F test which shows a significance value of 0.002 less than 0.005 which means that reading ability and learning motivation have a stealth effect on students' problem-solving ability in story problems. Reading ability and learning motivation contributed 38.3% to students' problem-solving ability in story problems and 61.7% were influenced by other variables that were not studied in this study.